Surface-Enhanced Raman Spectroscopy Analysis of Astragalus Saponins and Identification of Metabolites After Oral Administration in Rats by Ultrahigh-Performance Liquid Chromatography/Quadrupole Time-of-Flight Mass Spectrometry Analysis - Kong, Shengnan; Ou, Shan; Liu, Yan; Xie, Minzhen; Mei, Ting; Zhang, Yingshuo; Zhang, Jincheng; Wang, Qi; Yang, Bingyou (Frontiers in Pharmacology, 2022)
Astragalus mongholicus Bunge [Fabaceae] is an ancient Chinese herbal medicine, and astragalus saponins are the main active components, which have a wide range of biological activities, such as immunomodulation, antioxidation, neuroprotection and so on. In this study, silver nanoparticles obtained by sodium borohydride reduction were used as the enhanced substrate to detect astragaloside I (1), astragaloside II (2), astragaloside III (3), astragaloside IV (4), isoastragaloside I (5), and isoastragaloside II (6) in the phloem, xylem, and cork by surface-enhanced Raman spectroscopy (SERS). In the SERS spectrum of astraglus slices, the characteristic peaks were observed at 562, 671, 732, 801, 836, 950, 1026, 1391, 1584 cm-1, among which 950 cm-1 and 1391 cm-1 were strong SERS signals. Subsequently, the metabolites of the six kinds of astragalus saponins were identified by UPLC/ESI/Q-TOF-MS. 80, 89 and 90 metabolites were identified in rat plasma, urine and feces, respectively. The metabolism of saponins mainly involves dehydration, deacetylation, dihydroxylation, deoxylosylation, deglycosylation, methylation, deacetylation and glucoaldehydration. Ten metabolites (1-M2, 1-M11, 2-M3, 2-M12, 3-M14, 4-M9, 5-M2, 5-M17, 6-M3, and 6-M12) were identified by comparison with reference standards. Interestingly, astragalus saponins 1, 2, 5, and 6 were deacetylated to form astragaloside IV (4), which has been reported to have good pharmacological neuroprotective, liver protective, anticancer and antidiabetic effects. Six kinds of active astragalus saponins from different parts of Astragalus membranaceus were identified by SERS spectroscopy. Six kinds of active astragalus saponins from different parts of Astragalus membranaceus were identified by SERS spectrum, and the metabolites were characterized by UPLC/ESI/ Q-TOF-MS, which not only provided a new method for the identification of Traditional Chinese medicine, but also provided a theoretical basis for the study of the pharmacodynamic substance basis of astragalus membranaceus saponins.